Manajemen Program Komunitas Belajar Sekolah untuk Peningkatan Kompetensi Pedagogik Guru di SMP Negeri 1 Biatan - Baco, Asmar; Tunggal, Anggunan; Prasetyo, Teguh; Warman, Warman; Fitriadi, Ahmad (Jurnal Indragiri Penelitian Multidisiplin, 2025)
The School Learning Community (SLC) Program at SMP Negeri 1 Biatan is designed to enhance teacher and educational staff competencies through a collaborative approach. This program aims to reduce disparities in teacher competencies, create a supportive learning environment, and build professional networks. Implementation involves regular meetings where teachers take turns as resource persons to share best practices, experiences, and solutions to teaching challenges. The research findings indicate that the program successfully improves teachers' pedagogical competencies, particularly in classroom management, differentiated instruction, and assessment. The support of the school principal as an instructional leader has proven to be a key factor in the program's success, particularly in increasing teacher participation. The program is systematically evaluated to assess its effectiveness and provide feedback for further development. It has fostered a sustainable collaborative learning culture and positively impacted teachers' enthusiasm for teaching. The program's success demonstrates that a collaborative approach can effectively support teacher competency development. This study recommends that similar programs require thorough planning, sufficient human and financial resources, and government recognition to enhance teacher motivation and participation